Income Disparities in BRICS Economies: Analyzing the Role of Capital Account Liberalization and Foreign Bank Ownership - Ullah, Imran; Tunio, Fayaz Husain; Younas, Waqar (Annals of Human and Social Sciences, 2024)
This study rigorously examines the impacts of capital account liberalization and foreign bank ownership on income inequality within BRICS economies from 1995 to 2017. Prior literature presents divergent views on the effects of financial liberalization and foreign bank penetration on income distribution, prompting the need for a focused analysis in the BRICS context. Employing panel data methodologies, including Baseline Panel Regression, Arellano-Bond, and Arellano-Bover approaches, this research ensures robustness through comprehensive sensitivity analyses and robustness checks. Empirical findings demonstrate that capital account liberalization exerts a significant negative influence on income inequality, suggesting its role in reducing income disparities. Conversely, the presence of foreign bank ownership is associated with a statistically significant increase in income inequality. These results highlight the complex effects of financial policies on income distribution. Consequently, the study recommends that BRICS countries pursue sustainable capital account liberalization and strategically regulate foreign bank ownership, underpinned by robust economic and political governance, to effectively address income inequality.